Green supply chain management in construction: A systematic literature review and future research agenda - Badi, Sulafa (2019)
The construction industry is responsible for significant environmental impact. Mounting ecological and societal concerns are driving construction to ‘go green’. Green supply chain management offers the potential of a systemic approach to facilitate transformation of the sector. Research on green supply chain management in construction has been growing in recent times but to date has not been systematically brought together. A systematic literature review (SLR) is presented, applying the high standards of rigour and transparency required by the methodology. From an initial search result of 207 papers, 44 were included in the detailed analysis. The papers are described in terms of publication outlet, date of pub lication, geographic setting, methods used, tools and techniques, conceptual definition, the role of stakeholders and practical implications. The findings are synthesized to propose a categorization of approach and a comprehensive definition of green supply chain management in construction. An agenda for future research is outlined which emphasizes the need for an end-to-end perspective, engagement with the unique characteristics of the industry, a focus on the ultimate goals of environmental sus tainability, and on gaps in practical guidance, use of insights from relevant theoretical perspectives, and expansion to include critical stances.